Changes in ADMA/DDAH Pathway after Hepatic Ischemia/Reperfusion Injury in Rats: The Role of Bile. (26th August 2014) - Ferrigno, Andrea; Rizzo, Vittoria; Bianchi, Alberto; Di Pasqua, Laura G.; Berardo, Clarissa; Richelmi, Plinio; Vairetti, Mariapia
Abstract : We investigated the effects of hepatic ischemia/reperfusion (I/R) injury on asymmetric dimethylarginine (ADMA, a nitric oxide synthase inhibitor), protein methyltransferase (PRMT) and dimethylarginine dimethylaminohydrolase (DDAH) (involved, resp., in ADMA synthesis and degradation), and the cationic transporter (CAT). Male Wistar rats were subjected to 30 or 60 min hepatic ischemia followed by 60 min reperfusion. ADMA levels in serum and bile were determined. Tissue ADMA, DDAH activity, DDAH-1 and CAT-2 protein, DDAH-1 and PRMT-1 mRNA expression, GSH/GSSG, ROS production, and lipid peroxidation were detected. ADMA was found in bile. I/R increased serum and bile ADMA levels while an intracellular decrease was detected after 60 min ischemia. Decreased DDAH activity, mRNA, and protein expression were observed at the end of reperfusion. No significant difference was observed in GSH/GSSG, ROS, lipid peroxidation, and CAT-2; a decrease in PRMT-1 mRNA expression was found after I/R. Liver is responsible for the biliary excretion of ADMA, as documented here for the first time, and I/R injury is associated with an oxidative stress-independent alteration in DDAH activity. These data are a step forward in the understanding of the pathways that regulate serum, tissue, and biliary levels of ADMA in which DDAH enzyme plays a crucial role.